The relationship between pelvic inclination and muscles, function and length in healthy females - Mitra Haji Maghsoudi; Nasrin Naseri; Fatemeh Hosseini Ghahi; Zahra Fakhari (Vesnu Publications, 2013)
Introduction: Pelvic tilt is defined as pelvic inclination relative to the horizontal plane. The muscular strength and flexibility of lumbo pelvic region are effective factors in pelvic tilt. Studiesonthe relationship between muscle flexibility/strength and pelvic tilt have yieldedcontroversial results.The aim of this study was to examine this relationship in a larger sample and with more precise and sensitive instruments. Materials and Methods: 180 healthy women (20-65 years) participated in this study. Pelvic tilt was measured via inclinometer andmuscle function was determined throughisometric strength andendurance recordings for whicha dynamometer and a chronometer were used respectively. Muscles flexibility was evaluatedby special tightness tests. Results: There was little relationship between pelvic tilt and hip external and internal rotators strength as well as the flexibility of iliopsoas muscle. Also, pelvic tilt and trunk flexors and side flexors endurance were weakly correlated. Conclusion: According to the lumbo-pelvic muscles connections, it seems that the flexibility and strength of these muscles canaffect pelvic tilt. However, this effect was not provedin this study. Many of these muscles act on two or more joints, so they can show the effect of strength and length changes in other areas. Also the subjects of this study were healthy without any pathology and, considering flexibility and strength, werenot in abnormal range. These reasons may explain why the above-mentioned was not observed. Keywords: Pelvic tilt, Muscles length, Muscles flexibility, Muscle strength